Pengaruh Model Pembejaran Schema Based Instruction (SBI) Berbantuan Flash Card Terhadap Literasi Sains IPAS Siswa Kelas IV - Anggraini, Loni Tiya; Koderi; Muhammad Muchsin Afriyadi (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effect of the Schema Based Instruction (SBI) learning model assisted by flash cards on the scientific literacy in Ilmu Pengetahuan Alam dan Sosial (IPAS) of fourth-grade students at MIN 3 Bandar Lampung. The study employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The sample consisted of two classes, namely an experimental class and a control class, selected using a saturated sampling technique in which all members of the population were included as the research sample. Data were collected through a scientific literacy test and documentation. The research instrument was a scientific literacy test developed based on the indicators of explaining scientific phenomena, interpreting scientific data and evidence, and drawing inferences and making scientific predictions. The data were analyzed using normality and homogeneity tests, followed by an Independent Samples t-test. The results showed that the average scientific literacy score of students in the experimental class was higher than that of the control class. Furthermore, the hypothesis testing indicated a significant effect of the Schema Based Instruction (SBI) learning model assisted by flash cards on students' scientific literacy in IPAS. These findings suggest that the Schema Based Instruction (SBI) learning model assisted by flash cards is effective in improving students' scientific literacy. This study implies that the implementation of a schema-based learning model supported by visual media can serve as an effective alternative strategy for enhancing scientific literacy in IPAS learning at the elementary school level.